Hadron production in diffractive deep-inelastic scattering - Adloff, C; Aid, S; Anderson, M; Andreev, V; Andrieu, B; Arkadov, V; Arndt, C; Ayyaz, I; Babaev, A; Bahr, J; Ban, J; Baranov, P; et al. (1998)
Characteristics of hadron production in diffractive deep-inelastic positron-proton scattering are studied using data collected in 1994 by the H1 experiment at HERA. The following distributions are measured in the centre-of-mass frame of the photon dissociation system: the hadronic energy flow, the Feynman-x (xF) variable for charged particles, the squared transverse momentum of charged particles (p*T2), and the mean p*T2 as a function of xF. These distributions are compared with results in the γ * p centre-of-mass frame from inclusive deep-inelastic scattering in the fixed-target experiment EMC, and also with the predictions of several Monte Carlo calculations. The data are consistent with a picture in which the partonic structure of the diffractive exchange is dominated at low Q2 by hard gluons. © 1998 Elsevier Science B.V. All rights reserved.